SAT0467 Long Term Outcome and Foki VDR Polimorphism in JIA Patients on Anti-TNF Treatment. (23rd January 2014) - Vojinovic, J.; Jeftovic, T.; Lazaraevic, D.; Susic, G.
Abstract : Background: C ontribution of FoxI VDR (vitamin D receptor) polymorphism on disease outcome in JIA is not yet well established. Objectives: To investigate influence of FoxI VDR polymorphism on long term outcome in JIA patients. Methods: FokI VDR polymorphism was evaluated using the PCR-RFLP method in 82 JIA patients included in Serbian JIA registry treated with anti-TNF agent (etanercept) and 20 helthy controls. Observational period was 6 years. Results: Disease subtype distribution was 6.78% systemic, 54.24% poly RF- and extended oligo, 18.64% poly RF+, 16.95% ERA and 3.38 PsA. During follow up period 47, 8% of pts. could stop treatment after average of 33 months (12-60 months) and achieved remission which have lasted 13, 72 (2-48) months at cut off point. At the time cut off point 52, 2 % of the pts. were still under biologic treatment with average treatment duration 42 (12-79) months while 37, 5% of them could not stop treatment at any time point and 62, 5% achieved short time remission which lasted 12, 71 (2-48) months. Extended oligo and ERA JIA subtype significantly correlated with need to continue biologic treatment. The distribution of VDR genotypes was not significantly different among JIA subtypes. VDR genotypes distribution was 51.6% FF, 38.7% Ff and 9.7% ff while in 20 healthy controls only FF (wild type) genotype was present. Presence of f genotype significantly correlated with worse outcome and disease severity. Conclusions: Our results indicate that JIA patients, more frequently than healthy controls, have Ff or ff VDR FokI polymorphism. Presence of f variant for FokI polymorphism of VDR in JIA patients was associated with worse outcome and longer need for biologic treatment. Disclosure of Interest: None Declared